Efeito do tratamento padrão com atropina e pralidoxima na prevenção das alterações comportamentais e bioquímicas após intoxicação aguda pelo organofosforado clorpirifós - Siqueira, Alciene Almeida (2016)
Organophosphorus insecticides (OP), used in agriculture in many countries worldwide, exert their toxicity by inhibiting the activity of both central and peripheral cholinesterases, leading to the accumulation of acetylcholine at cholinergic synapses. Clinical studies have shown that chronic exposure to OP at low doses can induce affective disorders such as depression. Our research group verified that acute poisoning by one of those agents, chlorpyrifos (CPF) 20mg/kg, induced a depressivelike behaviour in adults male Wistar rats on the Forced Swimming Test (FST). Standard treatment for OP poisoning involves the use of atropine (ATR), a muscarinic antagonist, to treat the symptoms of cholinergic syndrome and a reativator of cholinesterases, such as pralidoxime (2-PAM), to restore the peripheral enzymatic activity. Thus, our aim was to assess if standard treatment would attenuate or reverse behavioral and biochemical changes in the FST, plasma, hippocampus, striatum and prefrontal cortex of rats 24 hours and 30 days after acute exposure to CPF. Animals were submitted to pre-exposure in the FST and immediately after they received intraperitoneal injections of CPF or saline (SAL). One hour later, animals were evaluated with regards to acute toxicity and then they were treated with SAL, ATR 10 mg/kg, 2-PAM 40mg/kg or ATR+2-PAM. Acute toxicity evaluation was carried out hour to hour for up to 4 hours after CPF or SAL injections. Twenty-four hours post-poisoning, half of the animals were decapitated in order to collect blood for determination of plasma cholinesterase (ChE) activity and the brain were dissected for determination of acetylcholinesterase (AChE) activity related to this time. The other half of animals was submitted to the sessions test (24 hours) and re-test (30 days after poisoning) in the FST, in which was measured the immobility time (in seconds) for 5 minutes. After the re-test session, the animals were decapitated and samples were collect for determination of cholinesterase activity 30 days after acute poisoning. CPF induced signs of acute toxicity and decreased plasma ChE activity .CPF increased immobility time in the test session (a depressivelike effect), but not in the re-test (30 days). ATR attenuated the depressive-like effect of CPF. 2-PAM reactivated AChE in the prefrontal cortex but not in the hippocampus and striatum 24 hours after poisoning. Thirty days later, behavioral and biochemical changes were absent. These results show that: (1) Behavioral and biochemical changes induced by CPF were transient and partially reversed by treatment with ATR and 2-PAM; (2) The possible accumulation of ACh by hippocampal AChE inhibition seems to be related to increased immobility time on the FST. This study suggests that even acute poisoning within a short period of time may impair mental health of subjects exposed to OP. It also suggests that the standard treatment for OP poisoning seems to be insufficient to reverse all of the changes caused by the OP exposure.